The Effect of Kangaroo Mother Care on Body Temperature Stability in Low Birth Weight Infants in the NICU - Septi Viantri Kurdaningsih; Dewi Rubi Fitriani; Mareyke Yolanda Lusia Sepang (Professional Evidence-based Research and Advances in Wellness and Treatment, 2025)
Infants with low birth weight (LBW) are prone to body temperature instability due to immature temperature regulation systems. Conventional care in incubators often causes mother-infant separation. Kangaroo Mother Care (KMC) is an innovative method that promotes closeness between mother and infant. This study aims to assess the effect of KMC on body temperature stability in LBW infants admitted to the NICU. Using a quantitative pre-experimental design with a one-group pretest-posttest approach, LBW infants meeting inclusion criteria were observed. Body temperature was measured before and after KMC implementation using a digital thermometer. Data analysis employed a paired t-test. Results showed that Prior to the implementation of KMC, the average body temperature of LBW infants was 36.7°C with a standard deviation of 0.159, ranging from 36.5°C to 37.2°C. After the implementation of KMC, the average body temperature increased to 37.3°C, with a standard deviation of 1.024, and a temperature range of 37.1°C to 37.5°C, with a p-value of 0.000 (p < 0.05). These findings indicate that KMC positively affects body temperature stability in LBW infants in the NICU. KMC is a nonpharmacological alternative to incubator care that improves LBW infant outcomes. It supports temperature stability, weight gain, respiratory regulation, and enhances the mother–infant bond. Routine implementation in NICUs can lower hospitalization duration, reduce reliance on medical equipment, and cut treatment costs. Successful adoption requires trained health personnel and supportive hospital policies to make KMC a standard part of neonatal care.